New naphtho[1,8-ef]perimidines: synthesis, fluorescence studies and application for detection of nitroanalytes - Igor L. Nikonov; Leila K. Sadieva; Мaria I. Savchuk; Еkaterina S. Starnovskaya; Dmitry S. Kopchuk; Igor S. Kovalev; Grigory А. Кim; Oleg N. Chupakhin (Chimica Techno Acta)
A rational approach to the synthesis of substituted naphtho[1,8-ef]perimidines based on SNH methodology and cyclization  reaction in the series of condensed azines with naphthalene substituents was presented. Photophysical properties of the obtained fluorophores were studied, in particular, green fluorescence in the 485–536 nm range with quantum yield up to 32.4% was detected. HOMO-LUMO energy values and distributions for the new compounds were calculated by the DFT method in comparison with nitroanalytes and perylene. Based on the data obtained, as well as on the results of fluorescence titration, the possibility of using the new diazaperylenes as potential chemosensors for the visual detection of nitro-containing explosives was shown.